Methodological challenges for music therapy controlled clinical trials in palliative care - Warth, Marco; Keßler, Jens; Koenig, Julian; Hillecke, Thomas; Wormit, Alexander F.; Bardenheuer, Hubert J. (Nordisk tidsskrift for musikkterapi, 2015)
Since the late 1970s, music therapy has been an important part of multidisciplinary palliative care programs. Despite its wide application and high acceptance by patients, caregivers and staff members, recent systematic reviews and reports point to a lack of research, and the need for controlled clinical trials. The present article reviews the methodological quality of controlled clinical trials on the effects of music therapy in palliative care and addresses issues regarding the implementation of such designs. We identified eight studies (both published and unpublished), conducted between 2003 and 2013, through a systematic search of the scientific literature. We present major challenges according to the PICOS taxonomy and provide recommendations for future research using controlled clinical trial designs.
Published online: 20 December 2014
Gesehen am 29.06.2020